Dimethyl Fumarate Alleviates NLRP3 Inflammasome Activation in Microglia and Sickness Behavior in LPS-Challenged Mice - Tastan, Bora; Arioz, Burak I.; Tufekci, Kemal Ugur; Tarakcioglu, Emre; Gonul, Ceren Perihan; Genc, Kursad; Genc, Sermin (Frontiers in Immunology, 2021)
NLRP3 inflammasome activation contributes to several pathogenic conditions, including lipopolysaccharide (LPS)-induced sickness behavior characterized by reduced mobility and depressive behaviors. Dimethyl fumarate (DMF) is an immunomodulatory and anti-oxidative molecule commonly used for the symptomatic treatment of multiple sclerosis and psoriasis. In this study, we investigated the potential use of DMF against microglial NLRP3 inflammasome activation both in vitro and in vivo. For in vitro studies, LPS- and ATP-stimulated N9 microglial cells were used to induce NLRP3 inflammasome activation. DMF’s effects on inflammasome markers, pyroptotic cell death, ROS formation, and Nrf2/NF-κB pathways were assessed. For in vivo studies, 12–14 weeks-old male BALB/c mice were treated with LPS, DMF + LPS and ML385 + DMF + LPS. Behavioral tests including open field, forced swim test, and tail suspension test were carried out to see changes in lipopolysaccharide-induced sickness behavior. Furthermore, NLRP3 and Caspase-1 expression in isolated microglia were determined by immunostaining. Here we demonstrated that DMF ameliorated LPS and ATP-induced NLRP3 inflammasome activation by reducing IL-1β, IL-18, caspase-1, and NLRP3 levels, reactive oxygen species formation and damage, and inhibiting pyroptotic cell death in N9 murine microglia via Nrf2/NF-κB pathways. DMF also improved LPS-induced sickness behavior in male mice and decreased caspase-1/NLRP3 levels via Nrf2 activation. Additionally, we showed that DMF pretreatment decreased miR-146a and miR-155 both in vivo and in vitro. Our results proved the effectiveness of DMF on the amelioration of microglial NLRP3 inflammasome activation. We anticipate that this study will provide the foundation consideration for further studies aiming to suppress NLRP3 inflammasome activation associated with in many diseases and a better understanding of its underlying mechanisms.